2004
DOI: 10.1677/jme.1.01600
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gonadotropin subunit gene transcription

Abstract: Reproductive function in mammals is regulated by the pituitary gonadotropins luteinizing hormone (LH) and follicle-stimulating hormone (FSH). LH and FSH are secreted by the gonadotrope cell and act on the gonad in a sequential and synergistic manner to initiate sexual maturation and maintain cyclic reproductive function. The synthesis and secretion of LH and FSH are regulated mainly by the pulsatile release of the hypothalamic decapeptide hormone gonadotropin-releasing hormone (GnRH). The control of differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
131
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(140 citation statements)
references
References 194 publications
1
131
0
6
Order By: Relevance
“…Similar to those in mammals (Gharib et al 1990, Burger et al 2004, the secretion and expression of fish gonadotropins are controlled by both neuroendocrine factors from the hypothalamus such as gonadotropin-releasing hormone (GnRH; Peter et al 1986, Weltzien et al 2004, Ando & Urano 2005 and steroids from the gonads (Kobayashi et al 1987, Dickey & Swanson 1998. Our previous study in the goldfish demonstrated that in addition to the neuroendocrine and endocrine regulation, pituitary gonadotropins are also subject to local paracrine regulation by activin (Yam et al 1999a, Yuen & Ge 2004, similar to the situation in mammals (Roberts et al 1989, Corrigan et al 1991, Bilezikjian et al 2004.…”
Section: Introductionmentioning
confidence: 80%
“…Similar to those in mammals (Gharib et al 1990, Burger et al 2004, the secretion and expression of fish gonadotropins are controlled by both neuroendocrine factors from the hypothalamus such as gonadotropin-releasing hormone (GnRH; Peter et al 1986, Weltzien et al 2004, Ando & Urano 2005 and steroids from the gonads (Kobayashi et al 1987, Dickey & Swanson 1998. Our previous study in the goldfish demonstrated that in addition to the neuroendocrine and endocrine regulation, pituitary gonadotropins are also subject to local paracrine regulation by activin (Yam et al 1999a, Yuen & Ge 2004, similar to the situation in mammals (Roberts et al 1989, Corrigan et al 1991, Bilezikjian et al 2004.…”
Section: Introductionmentioning
confidence: 80%
“…The consequences of modifying these secretion pathways have not been tested in vivo. In the pituitary, GnRH pulse characteristics are critical for differential regulation of LH and FSH (30)(31)(32)(33). Emerging evidence suggests GnRH pulses are interpreted at the level of gonadotropin β-subunit promoters, downstream signaling cascades involving MAPKs and ultimately reflected in corresponding subunit biosynthesis (31,33).…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of gonadotropin subunits in the anterior pituitary is mainly stimulated by gonadotropin-releasing hormone (GnRH) secreted from neurons which extend to the pituitary by way of the hypothalamus (15)(16)(17)(18)(19). GnRH binds to its specific receptor on the membrane of pituitary gonadotropes, and activates several signaling pathways involving PKC, PKA, MAPKs, and calcium/calmodulin-dependent protein kinases (16).…”
mentioning
confidence: 99%
“…GnRH binds to its specific receptor on the membrane of pituitary gonadotropes, and activates several signaling pathways involving PKC, PKA, MAPKs, and calcium/calmodulin-dependent protein kinases (16). The activated kinases modulate the action of transcription factors and repressors located downstream to regulate the expression of gonadotropins in a subunit-specific manner (17)(18)(19). Our recent study has suggested that TCDD suppresses GnRH-mediated PKC and PKA and/or their downstream mechanisms in cultivated fetal pituitary to attenuate gonadotropin synthesis (20).…”
mentioning
confidence: 99%